Development of a modified method for sequencing high G:C regions in chicken anemia virus genome - Chowdhury, S.M.Z.H.; Omar, A.R.; Aini, I.; Hair-Bejo, M. (Taylor & Francis, 2002)
Two areas in the chicken anemia virus (CAV) genome have high G:C content with secondary structures. These two G:C rich areas could not be sequenced with Perkin Elmer's Big Dye Terminator Cycle Sequencing Kit. Several modifications were carried out to solve the problem. Finally, a package of modified method was developed to sequence the high G:C areas. The result showed that the Perkin Elmer's Big Dye Terminator Cycle Sequencing Kit with the normal procedures are not suitable for sequencing the high G:C regions of the CAV genome. The present developed method made the Perkin Elmer's Kit useful for the first time to sequence the G:C rich hairpin structures of the CAV genome. The system may be useful to sequence all other G:C rich DNA templates.